Reconstructive trends following mastectomies in Scotland: A comparison with England. Issue 4 (August 2021) - Robertson, Bernard F.; Campbell, Esther Jennifer; Armstrong, Matthew; Malyon, Andrew
Abstract: Introduction: In England there has been a substantial increase in the use of immediate implant-based reconstruction, accounting for over half of all immediate reconstructions (IR). Less than one third of patients in England undergo autologous reconstruction IR. Our aim was to examine IR trends in Scotland. Methods: Data was extracted from the Scottish Morbidity Record held at the Information Services Division of the NHS National Services Scotland. All patients discharged from Scottish hospitals between 2011 and 2016 who had a diagnosis of breast cancer including DCIS and underwent mastectomy were identified. Patients undergoing IR were identified by coding at the time of mastectomy to identify who had IR and what method was used. Results: Between 2011 and 2016, 7358 patients underwent a mastectomy for breast cancer. 1845 patients (25%) had an IR. The percentage of patients undergoing IR increased from 22% in 2011 to 26% in 2016. The dominant annual procedure type was autologous reconstruction (free flap and pedicled flaps), accounting for 58% in 2011 and 54% in 2016. Pedicled flaps alone decreased from 40% in 2011 to 28% in 2016 and free flaps increased from 18% in 2011 to 26% in 2016. Implant based reconstruction rates were broadly consistent, 37% in both 2011 and 2016. Pedicled flaps with implant reconstruction decreased from 13% in 2011 to 5% in 2016. Conclusions: Autologous reconstruction (with increasing trend for free flaps procedures) remains a constant preferred technique for IR in Scotland, accounting for over half of IR performed. Highlights: Immediate reconstructions have increased in Scotland similar to England. Autologous reconstruction is most popular method in Scotland in contrast to England. Implant based reconstruction has increased in Scotland. Close links between breast and plastic surgery units may affect reconstructive trends.